BUILDING VOCABULARY THROUGH SONG AS EFFECTIVE METHOD IN LEARNING ENGLISH - Henni Rosa Triwardani (Lingua, 2022)
Abstract: This study aims to determine the effectiveness of songs in learning English vocabulary through quasi experiment method. The population is 287 students and used random sampling obtained for experimental class and control class. The research data gained is from English vocabulary test. Based on the instrument test, 10 items were valid and reliability was 0 ,346. Data analysis using application SPSS 23for windows.The results showed that the value of taccount 2.558 was highest than ttable 2.021 with a significance level (α) = 0.05 with db = 40. This shows that the value of taccount (th) was highest than ttable (tt) which means there was a significant difference in vocabulary learning between the experimental class and the control class.The average final score of the experimental class was 22.85, higher than the control class was 18.92. It could be concluded that the use of song media for learning English vocabulary is effective.